Analysis of the Thickness and Stability of Subsea Pipes in the Masela Block Working Area on Yamdena Island (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
Submarine pipeline is a transportation or concept used to transport hydrocarbon products such as crude oil and high-pressure natural gas. The fluid material or gas is pumped from the platform across the seabed using a pipeline. The Abadi Field in the Masela Block is one of the National Strategic Projects (PSN) located in the Tanimbar Islands Regency, Maluku Province. The block was developed by INPEX Masela Ltd. It geographically borders to Timor Leste and Australia. It was discovered in 2000 and contains potential gas reserves which reaching 10.73 trillion cubic feet (Tcf). This research aims to determine the minimum thickness of submarine pipelines, determine on-bottom stability in accordance with DNV RP-F109, and visualize the maximum pressure caused by significant current flow on the pipe surface by using Ansys Computational Fluid Dynamics 2023 R2 Student Version. This research method is used a quantitative. The analysis result of this research that have been obtained, the thickness of the pipe is 11.2 mm. The calculated of on-bottom stability is 0.012 for vertical and 0.008 for lateral stability. In Additionally, by using Ansys Computational Fluid Dynamics 2023 R2 Student Version, maximum pressure of the pipe is 14 Pa.
Keywords: Pipeline, Stability, Wall Thickness